2006
DOI: 10.1291/hypres.29.315
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Syndrome in Japanese Patients with Obstructive Sleep Apnea Syndrome

Abstract: We investigated the prevalence of metabolic syndrome in patients with obstructive sleep apnea syndrome (OSAS) referred to a tertiary university-based medical center. A cross-sectional study of patients with a definite diagnosis of OSAS was performed using new diagnostic criteria for metabolic syndrome that were

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
79
2
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(92 citation statements)
references
References 30 publications
(25 reference statements)
8
79
2
2
Order By: Relevance
“…The prevalence of MetS associated with nocturnal intermittent hypoxia was 2 to 3-fold higher for persons with a ODI of 5 to 15 and 4 to 5-fold higher for persons with an ODI of ≥ 15 compared with those with an ODI of 5. The magnitude of these associations was similar to those in previous studies of American and Chinese [7][8][9] . As for the components of MetS, previous studies reported that nocturnal intermittent hypoxia was associated with .…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The prevalence of MetS associated with nocturnal intermittent hypoxia was 2 to 3-fold higher for persons with a ODI of 5 to 15 and 4 to 5-fold higher for persons with an ODI of ≥ 15 compared with those with an ODI of 5. The magnitude of these associations was similar to those in previous studies of American and Chinese [7][8][9] . As for the components of MetS, previous studies reported that nocturnal intermittent hypoxia was associated with .…”
Section: Discussionsupporting
confidence: 89%
“…The prevalence of MetS defined by the Adult Treatment Panel guidelines of the National Cholesterol Education Program (NCEP/ ATP ) was 2-fold higher among patients with an apnea-hypopnea index (AHI) ≥ 5 than among those with AHI 5 7,8) , 2-to 4-fold higher among those with AHI ≥ 15 than among those with AHI 15 8,9) , and 9-fold higher among those with AHI ≥ 15 and OSA-related symptoms (e.g. excessive daytime sleepiness) than among those without either 10) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3). MetS is diagnosed in clinical practice by the NCEP-ATP (National Cholesterol Education ProgrammeAdult Treatment Panel) III criteria, which require the presence of three out of five criteria [36][37][38][39][40][41][42][43][44][45]. The number of MetS criteria is defined as the metabolic index and can be used as an indicator of severity of metabolic abnormalities.…”
Section: Osa Visceral Fat and The Metabolic Syndromementioning
confidence: 99%
“…In addition to elevated risk for CVD, MetS has been reported to be associated with diabetes mellitus (Ford et al 2008), chronic kidney disease (Ninomiya et al 2006), obstructive sleep apnea syndrome (Sasanabe et al 2006), and even mental disorders such as depression (Takeuchi et al 2009). In Japan, the Ministry of Health, Labour and Welfare estimated in 2007 that 7.6 million Japanese men (27%) and 2.9 million Japanese women (10%) aged 40-74 years met the criteria for a diagnosis of MetS (Ministry of Health, Labour and Welfare 2010).…”
mentioning
confidence: 99%